Dynamic control of endogenous metabolism with combinatorial logic circuits. Issue 11 (29th November 2018) - Moser, Felix; Espah Borujeni, Amin; Ghodasara, Amar N.; Cameron, Ewen; Park, Yongjin; Voigt, Christopher A.
Abstract: Controlling gene expression during a bioprocess enables real‐time metabolic control, coordinated cellular responses, and staging order‐of‐operations. Achieving this with small molecule inducers is impractical at scale and dynamic circuits are difficult to design. Here, we show that the same set of sensors can be integrated by different combinatorial logic circuits to vary when genes are turned on and off during growth. Three Escherichia coli sensors that respond to the consumption of feedstock (glucose), dissolved oxygen, and by‐product accumulation (acetate) are constructed and optimized. By integrating these sensors, logic circuits implement temporal control over an 18‐h period. The circuit outputs are used to regulate endogenous enzymes at the transcriptional and post‐translational level using CRISPRi and targeted proteolysis, respectively. As a demonstration, two circuits are designed to control acetate production by matching their dynamics to when endogenous genes are expressed ( pta or poxB ) and respond by turning off the corresponding gene. This work demonstrates how simple circuits can be implemented to enable customizable dynamic gene regulation. Synopsis: Genetically encoded sensors responding to feedstock (glucose), growth conditions (oxygen), and byproduct accumulation (acetate) are designed and their response is measured during growth. Sensor integration by combinatorial logic circuits generates different temporal responses and can be used to control metabolism. Genetically encoded sensors for glucose and oxygen are built based on synthetic Escherichia coli promoters that respond to native regulators and optimized using oligo synthesis and high‐throughput screening. As shown computationally, combinatorial logic circuits that implement different truth tables can integrate the three sensors to produce different dynamic responses during a growth experiment. The circuit output can be used to quickly and strongly repress a target gene by combining CRISPRi (transcriptional control) and a targeted protease (post‐translational control). Genetic circuits with CRISPRi/protease outputs were able to dynamically repress native target genes and regulate acetate metabolism. Abstract : Genetically encoded sensors responding to feedstock (glucose), growth conditions (oxygen), and byproduct accumulation (acetate) are designed and their response is measured during growth. Sensor integration by combinatorial logic circuits generates different temporal responses and can be used to control metabolism.